A Simplified Method for Modeling of Pressure Losses and Heat Transfer in Fixed-Bed Reactors with Low Tube-to-Particle Diameter Ratio - Tymoteusz Świeboda; Renata Krzyżyńska; Anna Bryszewska-Mazurek; Wojciech Mazurek; Alicja Wysocka (Energies, 2021)
This manuscript presents a simplified method of modeling fixed-bed reactors based on the porous medium. The proposed method primarily allows the necessity of precisely mapping the internal structure of the bed—which usually is done using real object imaging techniques (like X-ray tomography) or numerical methods (like discrete element method (DEM))—to be avoided. As a result, problems with generating a good quality numerical mesh at the particles’ contact points using special techniques, such as by flattening spheres or the caps method, are also eliminated. The simplified method presented in the manuscript is based on the porous medium method. Preliminary research has shown that the porous medium method needs modifications. This is because of channeling, wall effects, and local backflows, which are substantial factors in reactors with small values of tube-to-particle-diameter ratio. The anisotropic thermal conductivity coefficient was introduced to properly reproduce heat transfer in the direction perpendicular to the general fluid flow. Since the commonly used fixed-bed reactor models validation method based on comparing the velocity and temperature profiles in the selected bed cross-section is not justified in the case of the porous medium method, an alternative method was proposed. The validation method used in this work is based on the mass-weighted average temperature increase and area-weighted average pressure drop between two control cross-section of the reactor. Thanks to the use of the described method, it is possible to obtain satisfactorily accurate results of the fixed-bed reactor model with no cumbersome mesh preparation and long-term calculations.